Management of sickle cell disease in patients undergoing cardiac surgery. Issue 2 (16th January 2017) - Crawford, Todd C.; Carter, Michael V.; Patel, Rina K.; Suarez‐Pierre, Alejandro; Lin, Sophie Z.; Magruder, Jonathan Trent; Grimm, Joshua C.; Cameron, Duke E.; Baumgartner, William A.; Mandal, Kaushik
Abstract: Sickle cell disease is a life‐limiting inherited hemoglobinopathy that poses inherent risk for surgical complications following cardiac operations. In this review, we discuss preoperative considerations, intraoperative decision‐making, and postoperative strategies to optimize the care of a patient with sickle cell disease undergoing cardiac surgery.